The Influence of Instagram Marketing Content and Le Minerale Brand Image on Purchasing Decisions Mediated By Purchase Intention - Sardolian Simbolon; Ujang Sumarwan; Siti Jahroh (School of Business, IPB University (SB-IPB), 2024)
Background: Social media is one of the channels that can be used for digital marketing. Moreover, social media users continue to grow every year and have bright potential to market products while getting closer to consumers. Purpose: The study aims to analyze the perception of marketing content and brand image of Le Minerale bottled drinking water on consumer purchasing decisions. Design/methodology/approach: The method used in this research was SEM-PLS with the Smart PLS 3.3 application. The research focused on Le Minerale's Instagram followers, consisting of 259 respondents. Findings/results: The results of this study indicated that marketing content and Le Minerale brand image had a positive and significant effect on purchase intention, while purchase intention affected buying decisions. Among the marketing content indicators, persuasive indicators (KM3) had the strongest influence. Additionally, within the brand image variable, brand favorability as an indicator of CM2 exerted the strongest influence.Conclusion: Meanwhile, in the purchase intention variable, the indicator that had the strongest influence was interest (MB2). Additionally, several strategies could be applied to help Le Minerale compete more effectively and potentially become a market leader in the mineral water industry. These strategies included following the trend of viral content with close communication with consumers, conducting indirect marketing programs through various collaborations consistently, and maximizing other social media channels.Originality/value (State of the art): This research contributes to providing knowledge and strengthening the theory of how Instagram marketing content and a brand's brand image can influence buying decisions by mediation of purchase intention. The results of this study are also expected to be a reference in implementing digital marketing strategies, especially on Instagram social media. Keywords: brand image, content marketing, purchase decision, purchase intention, sem-pls